Development of copper-zinc-tin shape memory alloy by electroless plating - Alarcon, Maria Celine Poblete (2006)
Metal alloys which have the ability to return to their previous shape after application of heat are termed shape memory alloys (SMA). This phenomenon is driven by what is called a thermoelastic martensitic transformation, causing the crystal structure to undergo change at a certain temperature. At low temperatures, the crystal structure is twinned martensite. Upon deformation, the twinned martensite de-twins then transforms to austenite; this austenite phase has the same shape as that of the twinned martensite when sufficient heat is applied. The most common shape memory alloys are the nickel titanium and copper based alloys. Ni-Ti shape memory alloys, more frequently known as Nitinol, have superior mechanical properties but are expensive, which makes copper base alloys the more practical choice. Of the many possible copper based SMAs, the Cu-Zn, Sn system has been given relatively little attention. This research is therefore focused on the Cu-Zn-Sn system and aspires to develop a shape memory alloy through the relatively less common yet uncomplicated method of electroless plating, as opposed to a study which previously successfully fabricated Cu-Zn-Sn SMA by DC electroplating process.